The Real and the Imaginary in the Book Aja'ib al-Makhluqat wa Ghara'ib al-Mawjudat ' by Zakariya al-Qazwini (682 AH) - Salman Khazal, Researcher. Hussein; Hamza Abbas, Prof. Dr. Louay (Basra studies journal, 2024)
This research examines the theoretical and practical manifestations of reality and imagination in Zakariya ibn Muhammad al-Qazwini's book "Aja'ib al-Makhluqat wa Ghara'ib al-Mawjudat" (682 AH). The book exhibits significant variations between these two themes: reality serves as the foundational core, depicted through narratives and events grounded in historical contexts where al-Qazwini recounts the lives of caliphs, kings, ministers, incidents, and historical facts. However, he diverges from strict adherence to the structural norms of realism, such as specifying sources, events, time, and place, as elaborated in this study. Conversely, imagination holds a prominent role, encompassing terms like imaginative, strange, and extraordinary. This study focuses on the imaginative aspect, evident in al-Qazwini's use of fictional narratives and tales within the book. The imaginative element intertwines with reality, originating from factual material but challenging it by reshaping historical events into literary, aesthetic, and cognitive works that may or may not have occurred, crafted primarily for their artistic impact rather than factual accuracy.